Landholder Types in Leyte, the Philippines: A Review of Literature and Proposals for Methods to Extend Understanding - Emtage, Nicholas F. (Annals of Tropical Research, 2003)
Landholder typologies are potentially useful to assist in the design and administration of tree planting support programs. This paper reports a review of relevant literature on the nature of landholder types in regard to tree planting and upland farming in the Philippines, and some preliminary impressions of landholder types in several communities in Leyte on the basis of information obtained from visits to these communities in 2001. The potential research methodology to examine landholder attitudes and explore for the presence of distinct groups with respect to these attitudes in Leyte is examined.